2018
DOI: 10.1177/0885328218763866
|View full text |Cite
|
Sign up to set email alerts
|

Injectable TEMPO-oxidized nanofibrillated cellulose/biphasic calcium phosphate hydrogel for bone regeneration

Abstract: Nanofibrillated cellulose, obtained from rice straw agricultural wastes was used as a substrate for the preparation of a new injectable and mineralized hydrogel for bone regeneration. Tetramethyl pyridine oxyl (TEMPO) oxidized nanofibrillated cellulose, was mineralized through the incorporation of a prepared and characterized biphasic calcium phosphate at a fixed ratio of 50 wt%. The TEMPO-oxidized rice straw nanofibrillated cellulose was characterized using transmission electron microscopy, Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…Comparing these results with other cellulose-derived hydrogels loaded with calcium phosphate, TOCNFs CaP and TOCNFs CaPGO show a broader LVR. In contrast, the storage modulus values recorded are lower compared with the average G' values found in these studies [34][35][36]. This is probably a consequence of the higher inorganic content considered.…”
Section: Injectability Testcontrasting
confidence: 77%
See 1 more Smart Citation
“…Comparing these results with other cellulose-derived hydrogels loaded with calcium phosphate, TOCNFs CaP and TOCNFs CaPGO show a broader LVR. In contrast, the storage modulus values recorded are lower compared with the average G' values found in these studies [34][35][36]. This is probably a consequence of the higher inorganic content considered.…”
Section: Injectability Testcontrasting
confidence: 77%
“…Similar injectable hydrogels reported in the literature often require higher load values in order to be successfully extruded and/or lower extrusion speeds [ 30 , 39 ]. As an example, Safwat et al recently reported TOCNFs hydrogels loaded with a high amount of calcium phosphates which can be extruded trough a 18 G needle at 1.50 N; however, the extrusion speed was set to 1 mm min −1 , which is 36 times lower than the extrusion rate employed in this work, limiting the clinical applicability of the proposed composite [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…PLGA nanofibers have been used as carriers of antibiotics and combined with DBM to generate new bone formation in infected animal bone defects 277 . Nanofibrils made of cellulose have been used to produce injectable hydrogels 278 . Poly( l ‐lactide) (PLLA) nanosheets have been used for the controlled release of osteoinductive factors to treat critical‐sized defects in mice 279 successfully.…”
Section: Classificationmentioning
confidence: 99%
“…Besides, use of biodegradable polymeric materials such as PVA successfully eliminates the need for secondary surgery as they decompose inside the body corresponding to the bone regeneration rate . As opposed to pure polymeric hydrogels, composite hydrogel scaffolds can be customized to possess mechanical properties similar to those at the target site of its application, thereby leading to better biological responses, such as reduced stress shielding . An injectable composite system tends to integrate the benefits of a composite system with those of an injectable system .…”
Section: Introductionmentioning
confidence: 99%
“…The unique approach that has been undertaken in this work stems from natural bone matrix, as it is a heterogeneous natural composite material consisting of polymer matrix phase reinforced with organic nanofibrils. Collagen fibrils within the polymeric extracellular matrix (ECM) in the bone are always in the nanorange . Therefore, nanoenabled composite materials can play an important role to provide an appropriate environment for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%